Control volume method for hydromagnetic dynamos in non-uniformly stratified spherical shells - ŠIMKANIN, Ján (Contributions to Geophysics and Geodesy, 2008)
The numerical modelling of hydromagnetic dynamos in a rotating spherical shell using the control volume method is presented. The influence of non-uniform stratification and viscosity on hydromagnetic dynamo action has been investigated. The results indicate that the influence of non-uniform stratification of a spherical shell on hydromagnetic dynamos in the present geometric configuration is noticeable. Convection is columnar and runs in both stably and unstably stratified sublayers, although it is slightly suppressed in the stably stratified region. The generated magnetic fields are mostly dipole dominated. Temperature, pressure, velocity and magnetic fields are significantly modified mainly close to the outer boundary